Towards Teaching Contemporary Arabic Linguistics between (Theorizing and Application) - Djelloul, Sahli; Hicham, Khaldi (Arab Journal for Sciences and Research Publishing, 2020)
There is no doubt that language formed, through the chronological times of human existence, the basis for research and study in the various fields of the natural and human sciences, as they are not just sounds and signals with which every people communicates as he defined them (Ibn Jinni 922 AH - 392 AH), Or a set of structural functions of speech, as described centuries later (Ferdinand de Saussure 1857-1913) not only, but language transcends geographical and intellectual boundaries to verify and translate the epistemological content of man. We see the superiority of living languages ​​over other languages, and reaching this superiority requires reconsidering the important references of the language and integrating it with the developments of contemporary linguistic thought, and given the importance of the topic, this study came as an attempt to re-theorize comprehensively and purposefully in the educational field of the Arabic language, and it is worthy of us in this. The talk about the dream of realizing a contemporary Arabic linguistic thought befitting the status of the Arabic language, such as what was adopted and worked on by Professor (Abd al-Rahman Hajj Salih). Didactic reality lesson The Arabic linguist and its prospects, so we had to ask, saying, What are the stakes facing the development of the Arabic language? What are the most important theoretical and scientific alternatives relied upon in order to advance it globally? How can institutions and active bodies facilitate and market linguistic thought in the Arabic language to non-native speakers?